VITAMIN-D TOXICITY AND OTHER NON-MALIGNANT CAUSES OF HYPERCALCEMIA: A RETROSPECTIVE STUDY AT A TERTIARY CARE HOSPITAL IN PAKISTAN - Khan, Muhammad Naeem; Masood, Muhammad Qamar; Siddiqui, Muhammad Arsalan; Naz, Sabahat; Islam, Najmul (Journal of Ayub Medical College Abbottabad, 2017)
Background: Hypercalcemia is a common clinical problem; primary hyperparathyroidism and malignancy is commonest causes of hypercalcemia. Aetiology of hypercalcemia are changing, causes that were diseases of the past like Vitamin-D toxicity and milk alkali syndrome are observed more often. Vitamin-D deficiency is an important problem and overzealous replacement of Vitamin-D has been observed, suspected to cause toxicity. Method: This was a retrospective review of patients admitted at the Aga Khan University Hospital from January 2008 to December 2013 with hypercalcemia. We reviewed the electronic health records for laboratory and radiological studies, and discharge summaries to establish the cause of hypercalcemia. Patients with solid tumour malignancy were excluded from the analysis. The treatment records and hospital course of patients diagnosed with Vitamin-D toxicity were also reviewed. Results: Primary hyperparathyroidism was the most common cause of hypercalcemia comprising 41 (28.2 %) patients. Vitamin-D toxicity was present in 25 (17.3%) and probable Vitamin-D toxicity 11 (7.6 %) inpatients. Vitamin-D toxicity and probable Vitamin-D toxicity together comprised 36 (24.8%) cases. Other causes of hypercalcemia included multiple myeloma 18 (12.4%) patients, tuberculosis 6 (4.1%) patients, chronic kidney disease6 (4.1%) cases, sarcoidosis 4 (2.7%) and lymphoma 3 (2.0%) patients. In 29(20%) patients a cause of hypercalcemia could not be determined and were labelled as undiagnosed cases. Conclusion: Vitamin-D toxicity was the second commonest cause of hypercalcemia after primary hyperparathyroidism. Knowledge of the prevalent and emerging causes of hypercalcemia is important for prompt diagnosis and treatment. Keywords: Vitamin-D toxicity; Hyperparathyroidism; Hypercalcemia